Klovn for Livet - Grøn, Ida (Denmark : Sørensen, Byrge ; Köhncke, Anne, 2011)
The film follows a hospital clown named Angus in his daily activities with children and staff at the cancer ward in one of the biggest hospitals in Denmark. Angus has to deal with nearly unbearable situations on a daily basis. One of the children, six-year old Tobias, falls ill and Angus becomes a safe haven for him.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films